THE NEW PRODUCT DEVELOPMENT OF CIVIC HYBRID FOR LOW CARBON AUTOMOBILE: A CASE STUDY AT HONDA MALAYSIA SDN. BHD. - binti Md Yusof, Nur Izatul Iffah; Chew, Boon Cheong; Yu Xin, Ou Yang (Journal of Technology Management and Business, 2015)
Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. It contains within two keys concept: concept of ‘needs’ and the idea if limitatins imposed by the state of technology and social organization on the environment’s ability to meet present and future needs. Hybrid vehicle is a vehicle that uses two or more distinct power sourcs to move the vehicle which can be conventional internal combustion engine and also high voltage electric motor. This is known as low carbon vehicles. For the automakers in this industry, there are few causes that push their mind to go further for development: customer demand, new technological possibilities and regulation. However, it also cause problem in order to sustain hybric car in the market of sustainability when it need to compete with other types of propulsion. Hence, there are few factor that need to be considered to sustain the hybrid car: fuel efficient, green environmental and industrial growth. After the hybrid car enter the market, the company need to arrange for the strategize in order for it to sustain in the business sustainability. The company need to focus on research and development (R&D), strategic maket planning in high-tech firms and customer-driven innovation. At last, researcher suggested that the environmental education should passed by all parties and delivered directly to the society. one can somehow gain more knowledge and information about the technology of hybrids and indirectly contribute back to the society, automobile manufacturers and environment through knowledge sharing.